2021
DOI: 10.1186/s12889-021-10923-5
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic inequalities in hospital admissions in England: an observational study

Abstract: Background Ethnic inequalities in health are well-known and partly explained by social determinants such as poorer living and working conditions, health behaviours, discrimination, social exclusion, and healthcare accessibility factors. Inequalities are known both for self-reported health and for diseases such as diabetes, cardiovascular diseases, respiratory diseases, and non-specific chest pains. Most studies however concern individual diseases or self-reported health and do not provide an ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Identifying the precise pattern of interrelated causes underpinning our (and previous) findings is difficult, given the complex interplay between numerous biological, environmental, demographic, social, and healthcare related factors which have been suggested to explain ethnic differences in health outcomes [37,38]. However, as our data were obtained from admitted patients, it is worth noting that ethnic inequalities exist in hospital admission in England: investigating around 41 million hospitalisations between 2009 and 2014, Petersen et al showed large variations among ethnic groups in the age-and deprivation-adjusted overall and cause-specific number of admissions, particularly for CVDand diabetes-related hospitalisation [39]; therefore, information on CVD and type 2 diabetes from hospital data may reflect inequalities in the access to healthcare services rather than the population burden of these two conditions [40,41]. A further element to consider is the variable proportion of migrants among ethnics group [16]: as there is evidence that people who migrate to UK are generally healthier than UK-born population [42][43][44], variations in these proportions may contribute to the lower mortality rates in some ethnic groups.…”
Section: Discussionmentioning
confidence: 85%
“…Identifying the precise pattern of interrelated causes underpinning our (and previous) findings is difficult, given the complex interplay between numerous biological, environmental, demographic, social, and healthcare related factors which have been suggested to explain ethnic differences in health outcomes [37,38]. However, as our data were obtained from admitted patients, it is worth noting that ethnic inequalities exist in hospital admission in England: investigating around 41 million hospitalisations between 2009 and 2014, Petersen et al showed large variations among ethnic groups in the age-and deprivation-adjusted overall and cause-specific number of admissions, particularly for CVDand diabetes-related hospitalisation [39]; therefore, information on CVD and type 2 diabetes from hospital data may reflect inequalities in the access to healthcare services rather than the population burden of these two conditions [40,41]. A further element to consider is the variable proportion of migrants among ethnics group [16]: as there is evidence that people who migrate to UK are generally healthier than UK-born population [42][43][44], variations in these proportions may contribute to the lower mortality rates in some ethnic groups.…”
Section: Discussionmentioning
confidence: 85%
“…Other studies have shown that even when admission rates are adjusted for age and deprivation, discrepancies in admission rates across ethnic groups remain [13]. This supports that ethnic inequalities in health are driven by factors other than deprivation, including overall health and health-seeking behaviours alongside discrimination and marginalisation [13][14][15]. Addressing socioeconomic determinants of health is necessary but not sufficient to eliminate ethnic inequalities [42].…”
Section: Findings In Contextmentioning
confidence: 91%
“…Alongside an overall increased burden of disease, evidence suggests ethnic minorities may experience increased barriers to healthcare access and less effective healthcare provision [13][14][15]. It was found that ethnic minority groups may have less disease monitoring and slower intensification of therapy for certain chronic conditions [15].…”
Section: Findings In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that ethnic minorities are more vulnerable to a variety of long - term health problems. For instance, South Asians are at a higher risk of diabetes, coronary heart disease, asthma, gastrointestinal diseases while Black ethnic groups are at a higher risk of hypertension and diabetes [1]. Therefore, it is plausible that ethnic minorities dealing with a variety of health issues may exhibit their frustrations subconsciously on their patient satisfaction scores, consistently scoring negatively in comparison to the ethnic majority.…”
Section: Introductionmentioning
confidence: 99%